Association of Hospital Volume and Quality of Care With Survival for Ovarian Cancer. Issue 3 (September 2017) - Wright, Jason D.; Chen, Ling; Hou, June Y.; Burke, William M.; Tergas, Ana I.; Ananth, Cande V.; Neugut, Alfred I.; Hershman, Dawn L.
Abstract : OBJECTIVE: To assess whether strict adherence to quality metrics by hospitals could explain the association between hospital volume and survival for ovarian cancer. METHODS: We used the National Cancer Database to perform a retrospective cohort study of women with ovarian cancer from 2004 to 2013. Hospitals were stratified by annual case volume into quintiles (2 or less, 2.01–5, 5.01–9, 9.01–19.9, 20 cases or greater) and by adherence to ovarian cancer quality metrics into quartiles. Hospital-level adjusted 2- and 5-year survival rates were compared based on volume and adherence to the quality metrics. RESULTS: A total of 100, 725 patients at 1, 268 hospitals were identified. Higher volume hospitals were more likely to adhere to the quality metrics. Both 2- and 5-year survival increased with hospital volume and with adherence to the measured quality metrics. For example, 2-year survival increased from 64.4% (95% CI 62.5–66.4%) at low-volume to 77.4% (95% CI 77.0–77.8%) at high-volume centers and from 66.5% (95% CI 65.5–67.5%) at low-quality to 77.3% (95% CI 76.8–77.7%) at high-quality hospitals ( P <.001 for both). For each hospital volume category, survival increased with increasing adherence to the quality metrics. For example, in the lowest volume hospitals (two or less cases annually), adjusted 2-year survival was 61.4% (95% CI 58.4–64.5%) at hospitals with the lowest adherence to quality metrics and rose to 65.8% (95% CI 61.2–70.8%) at the hospitals with highest adherence to the quality metrics ( P <.001). However, lower volume hospitals with higher quality scores still had survival that was lower than higher volume hospitals. CONCLUSION: Although both hospital volume and adherence to quality metrics are associated with survival for ovarian cancer, low-volume hospitals that provide high-quality care still have survival rates that are lower than high-volume centers. Abstract : Survival rates for ovarian cancer are higher at high-volume hospitals, even after adjustment for quality of care.